Unbecoming subjects : Judith Butler, moral philosophy, and critical responsibility - Thiem, Annika (Fordham University Press, 2008)
Moral philosophy and post-structuralism have long been considered two antithetical enterprises. This book argues that Judith Butler's work makes possible a productive encounter between these two aspects of philosophy, rethinking responsibility and critique as key concepts at the juncture of ethics and politics.